HACIA UNA NUEVA PEDAGOGÍA EN LA EDUCACIÓN SUPERIOR - Helskog, Guro Hansen; TORGERSEN , GLENN-EGIL (Revista Internacional de Filosofía Aplicada HASER, 2021)
In this essay the authors argue the need for a new pedagogy in Higher Education (HE). Our hypothesis is that the predominant focus today is on instrumental systems meant to measure the “quality” of education, subjecting the HE-teacher to goal management and frameworks that limit didactic possibilities. However, acting wisely and solving challenges across professions in an increasingly unpredictable world, requires attitudes, knowledge, skills and understanding that cannot unambiguously be defined in advance. Using a reflective practice and action inquiry research approach, the authors reflect upon experiences and research involving the Dialogos approach to philosophical practice, new research findings in pedagogy for the unforeseen and data from the completion of a PhD course for employees from four faculties in higher education. We argue that higher education should focus on open-ended and creative approaches to teaching that includes philosophical practices and reflective “samhandling” across disciplines. All higher education study programmes should to some extent train students for unforeseen events in life and society.